2005
DOI: 10.1021/ja0425381
|View full text |Cite
|
Sign up to set email alerts
|

A Hydrophobic Nanocapsule Controls the Photophysics of Aromatic Molecules by Suppressing Their Favored Solution Pathways

Abstract: A combination of hydrophobic forces and guest templation drive the assembly of cavitands into molecular capsules. Remarkably, anthracene that dimerizes with unit efficiency in solution does not dimerize within the capsule despite forming 2:2 complex. The capsule allows an unprecedented examination of the anthracene excimer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
160
0
6

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 225 publications
(177 citation statements)
references
References 24 publications
11
160
0
6
Order By: Relevance
“…18 reported exceptions to the 55 AE 0.9% rule in rare cases with a maximum of 75%, while Bruce et al 19 observed a higher packing efficiency of 82% with deep cavity cavitands. The (2 Â 1,4-dioxane$2 Â H 2 O) 2 @(4(OTf) 4 ) 2 capsule thus represents one of the most dense dimeric capsules.…”
mentioning
confidence: 97%
“…18 reported exceptions to the 55 AE 0.9% rule in rare cases with a maximum of 75%, while Bruce et al 19 observed a higher packing efficiency of 82% with deep cavity cavitands. The (2 Â 1,4-dioxane$2 Â H 2 O) 2 @(4(OTf) 4 ) 2 capsule thus represents one of the most dense dimeric capsules.…”
mentioning
confidence: 97%
“…Selbstassemblierte molekulare Kapseln werden durch kovalente Bindungen gebildet [1] oder reversibel durch Wasserstoffbrücken, [2][3][4][5][6][7][8] Wechselwirkungen zwischen einem Metall und seinen Liganden [9,10] oder hydrophobe Effekte zusammengehalten. [11] Gäste liegen in Kapseln typischerweise in molaren Konzentrationen vor. Bei Anwesenheit von zwei oder mehreren Gästen besteht eine hohe Wahrscheinlichkeit dafür, dass diese miteinander wechselwirken und molekulare Anordnungen entstehen, die einer supermolekularen Chemie zweiter Ordnung [12] entsprechen ("Komplexe innerhalb von Komplexen"), oder miteinander reagieren [9b] und dabei sogar Reaktionswegen folgen, die in Lösung unwahrscheinlich sind.…”
unclassified
“…The emission peak at 515 nm is ascribed to the anthracene excimer emission, which is generally observed in the highly concentrated anthracene solution and film [27]. The excimer emission of the PMAn-Temp was stronger than that of PMAn synthesized from …”
Section: Optical Properties Of Synthesized Pmanmentioning
confidence: 92%